MO532: Cardiovascular Events in Patients With Non–Dialysis-Dependent Chronic Kidney Disease and Anemia: Regional Analysis of Patients Previously Treated With Erythropoiesis-Stimulating Agents in the PRO2TECT Trial. (3rd May 2022) - Parfrey, Patrick; Chertow, Glenn; Eckardt, Kai-Uwe; Burke, Steven; Luo, Wenli; Minga, Todd; Winkelmayer, Wolfgang
Abstract: BACKGROUND AND AIMS: Vadadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor being investigated for the treatment of anemia due to chronic kidney disease (CKD). In global phase 3 trials, vadadustat has demonstrated non-inferiority to darbepoetin alfa for time to major adverse cardiovascular event (MACE) in patients with dialysis-dependent CKD (INNO2VATE trials), but not with non–dialysis-dependent CKD (NDD-CKD; PRO2 TECT trials) [1, 2 ]. In a prespecified subgroup analysis of the PRO2 TECT trials, a difference in the relative safety between vadadustat and darbepoetin alfa was observed between the US and non-US regions [1 ]. We investigated regional differences in MACE in patients with NDD-CKD-administered vadadustat and darbepoetin alfa who were previously treated with erythropoietin-stimulating agents (ESAs) in the PRO2 TECT trials. METHOD: Two phase 3, open-label, randomized, active-controlled clinical trials comparing vadadustat with darbepoetin alfa were conducted in North America, Latin America, Europe, Africa, and the Asia-Pacific region. This post hoc analysis evaluated MACE in patients in the PRO2 TECT trial who were actively maintained on ESAs at study entry with ≥1 dose received within 6 weeks before or during screening (Conversion trial; NCT02680574) and who received ≥1 dose of trial drug, stratified by region (USA versus Europe versus non-US/non-Europe). MACE was defined as a composite of death from any cause, nonfatal myocardial infarction or nonfatal stroke. Expanded MACE was defined as MACE plus hospitalization for heart failure or thromboembolic event, excluding vascular access failure. RESULTS: A total of 1723 ESA-treated patients were randomized in the conversion trial of the PRO2 TECT program and received ≥1 dose of study drug, including 665 patients in the USA, 444 in Europe, and 614 outside the USA and Europe. Europe had a lower proportion of patients with diabetes and more patients who had received intravenous (IV) iron, while patients in the non-US/non-European region were younger and had a lower prevalence of cardiovascular (CV) disease. A higher proportion of patients in Europe were using darbepoetin alfa at baseline than in other regions (59%–63% versus 14%–28%), though ESA dose was lower (57–61 versus 93–149 IV epoetin equivalent U/kg/week). The hazard ratio for MACE in the overall population for vadadustat versus darbepoetin alfa was 1.16 (95% CI 0.93–1.45). Across regions, event rates were similar in the vadadustat groups, but event rates in the darbepoetin alfa group were lower in Europe compared with the US and non-US/non-Europe (Table 1 ), which was driven by fewer total deaths (non-CV and CV) reported in Europe in the darbepoetin alfa arm ( n  = 24/220) compared with the vadadustat arm ( n  = 38/224) (Table 2 ). Additional post hoc analyses of MACE accounting for several baseline characteristics, including ESA dose, did not alter the outcomes of the study. CONCLUSION: Regional differences in time to first MACE were observed in patients with NDD-CKD who were treated with ESA and randomized to receive vadadustat or darbepoetin alfa as part of the PRO2 TECT program. It remains unclear if the lower risk of MACE observed in Europe with the darbepoetin alfa group was related to differences in unobserved baseline characteristics, regional treatment practices, methodological reasons or chance.